The Effect of sprint interval training on testis oxidant/antioxidant status and reproductive indices of adult wistar rats - Mahmood Tajik Khaveh; Mohammad Rahmani; Ali Samadi (Shahid Beheshti University, 2023)
Background and Purpose: In contemporary modern societies a lot of people suffer from reproductive system dysfunction and infertility. Various factors such as sedentariness, some diseases and medicines play a role in incidence of reproductive dysfunction, which can lead to decreased reproductive capacity. One of the main mechanisms of which is the increased free radical's production and oxidative stress in testis. Sprint interval training (SIT) is one of the most time-efficient types of exercise comparing to other exercise methods, which could be used to promote physical activity level. The aim of the present study was to determine the effect of SIT on testis oxidant-antioxidant status and some reproductive indices in adult Wistar rats.Materials and Methods: In this experimental study, 16 adult male Wistar rats wereobtained and randomly divided into: 1) control and 2) training groups. Then, the training group practiced 3 times a week for eight weeks. Forty-eight hours after the last exercise session, the rats' testis were removed after anesthesia and transferred to the laboratory and the activities of superoxide dismutase (SOD) and glutathione peroxidase (GPX), as well as total antioxidant capacity (TAC) and malondialdehyde (MDA) levels were assessed. Moreover, main reproductive function indices including tubular differentiation index (TDI), spermiogenesis index (SI), and cumulative index (RI) were determined. Data were analyzed using independent samples t-test at the alpha = 0.05. Results: The statistical analysis revealed that the MDA level of the testis in the training group was significantly higher than the control group (P<0.001). There was no significant difference between groups in terms of the SOD activity and TAC. However, in the training group the GPX activity level was significantly higher comparing to the control group (P<0.05). Moreover, the number of Leydig cells, TDI, and RI in the training group were significantly lower in comparison with the control group (P˂0.05); Nevertheless, no significant difference was observed between groups in terms of SI (P>0.05).Conclusion: SIT may increase oxidative stress in the testicular tissue and negatively affect the main spermatogenic indices in testis, which can lead to reproductive dysfunction. Conducting more research in this area while controlling the other influential factors and training variables (intensity, duration, and volume) is recommended.